Flavonoid pada Buah Takokak (Solanum Torvum SW.): Tinjauan Sistematis Terhadap Kandungan dan Aktivitas Biologis (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Takokak fruit is a plant widely used as a food ingredient and herbal plant because it contains various secondary metabolite compounds, especially flavonoids. Flavonoids are known to have biological activity as antioxidants that play a role in warding off free radicals. This study aims to examine the flavonoid content in takokak fruit and its biological activity based on the results of previous studies. The method used is a Systematic Literature Review (SLR) with PRISMA guidelines through the process of identification, selection, and analysis of scientific articles from the Google Scholar, ScienceDirect, PubMed, and DOAJ databases. The results of the study indicate that takokak fruit contains flavonoids with varying levels, ranging from 11.965 mg/L to 199.2 mg QE/g depending on the extraction and analysis methods used. The flavonoid content in takokak fruit is known to have antioxidant, antibacterial, anti-inflammatory, and free radical scavenging activities. Differences in flavonoid levels are influenced by the type of solvent, extraction method, fruit ripeness level, and environmental conditions where the plant grows. This study shows that takokak fruit has the potential to be developed as a functional food ingredient and a source of herbal-based natural ingredients.